(untitled) (Research, Society and Development, 2023)
Introduction: Medication-related Osteonecrosis of the Jaw (MRONJ) is a condition that may affect patients undergoing oral surgery procedures that use antiresorptive drugs. It is essential that the Doctor of Dental Surgery (DDS) is familiar with the pathology and how to diagnose, prevent and approach it. Objectives: To perform a literature review on MRONJ and to guide the DDS on how to manage the affected patients. Methodology: a systematized search was conducted on the PubMed virtual database using the terms: "diphosphonates", "dentist’s practice pattern", "dentists", "dentist’s role" and "Bisphosphonate-Associated Osteonecrosis of the Jaw". 29 articles in English, published in the last 5 years, were included. Results and discussion: MRONJ is characterized by exposed and necrotic bone that persists for more than 8 weeks and happens in patients taking antiresorptive agents. It is multifactorial and its severity depends on the dosage, route of administration, and treatment duration. Its management must be multidisciplinary to improve the patient’s quality of life. The DDS must focus on prevention. Every patient should have their oral health evaluated before starting antiresorptive therapy and be informed of its risks and benefits. Most DDSs do not feel confident to adequately manage these cases, even though information on MRONJ is more widespread among younger DDSs and recent graduates. Conclusion: MRONJ is a harmful condition for the patient and it is the DDS’s responsibility to know how to treat and prevent it, by having adequate knowledge of this pathology and making decisions based on the latest scientific evidence.